Overview of the Compliance of Health Protocols Implementation in Preventing the Spread of Covid -19 - Ambar Dwi Erawati (GLOBAL HEALTH SCIENCE GROUP, 2021)
One of the government policies in handling Covid-19 is to bring order to the community in maintaining health protocols. Based on a preliminary survey conducted by researchers, there are differences in the implementation of compliance in rural and urban communities. Objective: This study was to determine the compliance in implementing health protocols. This research is a quantitative research conducted at Semarang City. Total sample of 400 respondents. How to take samples with incidental sampling by distributing google forms containing questionnaires that are distributed in several groups of whatshap groups with the help of 5 enumerators who have different characteristics (university and occupation) to avoid data bias in certain groups. The data will be analyzed descriptively by describing the frequency distribution Results: The majority of respondents at Semarang City have complied with health protocols, however the compliance is still due to enforcing regulations not because of awareness of maintaining health. The majority of respondents have complied with maintaining health protocols, but of the three health protocols the most adhered to are using masks.